1989
DOI: 10.1128/jb.171.2.1093-1099.1989
|View full text |Cite
|
Sign up to set email alerts
|

An rpoN-like gene of Alcaligenes eutrophus and Pseudomonas facilis controls expression of diverse metabolic pathways, including hydrogen oxidation

Abstract: Pleiotropic mutants of Alcaligenes eutrophus with the phenotype Hno-have been characterized previously.They are deficient in several diverse metabolic activities, including hydrogen oxidation, nitrate and urea assimilation, denitrification, and various substrate transport systems. Phenotypically similar mutants were identified among hydrogenase-deficient strains of Pseudomonas facilis. The TnS-labeled hno gene was cloned from a genomic DNA library of A. eutrophus and used to identify the corresponding unimpair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…Alternatively, P. syringae could have a single gene encoding glutamine synthetase, which requires 54 for the high-level expression needed for ammonia assimilation but which has sufficient basal expression to prevent auxotrophy. rpoN mutants of most soil bacteria, including Azotobacter vinelandii, P. putida, and Agrobacterium tumefaciens, are not glutamine auxotrophs (39,40,53,74,75).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, P. syringae could have a single gene encoding glutamine synthetase, which requires 54 for the high-level expression needed for ammonia assimilation but which has sufficient basal expression to prevent auxotrophy. rpoN mutants of most soil bacteria, including Azotobacter vinelandii, P. putida, and Agrobacterium tumefaciens, are not glutamine auxotrophs (39,40,53,74,75).…”
Section: Discussionmentioning
confidence: 99%
“…The structural genes for the a-and P-subunits of acetoin:2,6-dichlorophenolindophenol oxidoreductase (acoA and acoB, respectively); for the protein FMP (acoC), which seems to be a dihydrolipoamide acetyltransferase; and for a protein of yet unknown function (acoX) are probably organized in one single operon (acoXABC) which is localized on fragments A and C (36). Fragment B harbors an rpoN-like gene, and mutants carrying a TnS insertion in this gene exhibited an extremely pleiotropic phenotype (13,38). As these mutants * Corresponding author.…”
mentioning
confidence: 99%
“…Furthermore, the synthesis of both hydrogenases is temperature sensitive; hydrogenase synthesis is completely abolished above 33°C (10). The expression of both hydrogenase proteins depends on a chromosomal gene, designated hno, which controls a number of metabolic activities in A. eutrophus (34). Recent nucleotide sequence analysis indicated that hno encodes a54 of core RNA polymerase (50).…”
mentioning
confidence: 99%